Streptococcus pneumoniae - Fouch, Sarah (Henry Stewart Talks, 2024)
Characteristics of Streptococcus pneumoniae, Cell wall, Clinical manifestation: bacterial pneumonia, Virulence factors promote infection and spreading, Prevention and treatment